Commercial Banks' Credit Management and Bad Debt Problems - WÓJCIK-CZERNIAWSKA Agnieszka; NOWAK Jacek (Communications of International Proceedings, 2022)
Credit management monitors consumer payments. A credit management system can lower borrowers' cash. Credit management ensures a company's financial flow. There are five assumptions about a bank's performance, each of which can be affected by factors such as the Loan Loss Provision, the Loan to Deposit Ratio, the Equity to Asset Ratio, and Loan Write Off. Secondary information was utilized for the research methodology. Descriptive statistics, correlation, and OLSR are used to examine the information. Bank performance can be affected by factors such as loan loss provisions, non-performing loans, and equity as a percentage of assets. Credit risk management and bad debt procedures are essential for financial institutions. The profitability of a worldwide bank can be affected by indications of credit risk management. Findings from the study suggest that management at banks may use nonperforming loan provisions to smooth earnings, which might be a red flag for shareholders. Employing both internal and external auditors is one way for owners to mitigate the knowledge gap between themselves and their managers. The financial stability and ability to handle credit risk are two characteristics that set commercial banks apart from other types of financial institutions. The study indicated that capital adequacy ratios and the proportion of non-performing loans can have an impact on the financial health of commercial banks around the world. A commercial bank's bottom line can be improved by better credit risk management. Banks should implement a sound credit estimation before lending money to consumers and build up effective processes and regulations for the management and provision of credit, with careful monitoring of customer information, purpose, and ability to repay. Instead than only decreasing credit risk, banks should increase their competitiveness and performance.
Keywords: Credit risk management; bad debts; commercial banks; financial performance; non-performing loans